2022
DOI: 10.1097/mcg.0000000000001751
|View full text |Cite
|
Sign up to set email alerts
|

Older Age at First Screening Colonoscopy is Associated With an Increased Risk of Colorectal Adenomas and Cancer

Abstract: Introduction: The goal of colorectal cancer (CRC) screening is to detect precancerous polyps before cancer development or identification of cancer at an early stage. Guidelines have recommended screening colonoscopy to start at age 45. Our aim was to determine the impact of delays in performing the first screening colonoscopy on the risk of adenoma or CRC detection. Methods: We analyzed colonoscopy and histopathology data of average CRC risk patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Nowadays, it is critically relevant, especially in high-incidence geographic areas, to identify markers that allow us to select the population at risk of developing EOCRC, as most individuals younger than 50 years are not considered for CRC screening strategies, as they are part of the average-risk population [ 2 ]. In fact, it has been reported that older age at the time of screening colonoscopy is associated with an increased rate of detection of adenomatous polyps and CRC [ 7 ]. This highlights the need for adherence to guidelines to prevent the development of CRC, as well as the identification of useful markers to facilitate the early detection of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is critically relevant, especially in high-incidence geographic areas, to identify markers that allow us to select the population at risk of developing EOCRC, as most individuals younger than 50 years are not considered for CRC screening strategies, as they are part of the average-risk population [ 2 ]. In fact, it has been reported that older age at the time of screening colonoscopy is associated with an increased rate of detection of adenomatous polyps and CRC [ 7 ]. This highlights the need for adherence to guidelines to prevent the development of CRC, as well as the identification of useful markers to facilitate the early detection of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The older that patients start colonoscopy screening, the higher likelihood of detecting adenomatous polyps and CRC [14 ▪ ].…”
Section: Impact Of Health Insurance Poverty and Comorbiditiesmentioning
confidence: 99%